A Critical Review on Panchagavya – A Boon Plant Growth - K, Tharmaraj. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Panchagavya, a Vedic formulation for increased productivity, disease resistance in plants and potential of utilizing Panchagavya as biofertilizer was tested on various pulses Vigna radiate, Vigna mungo, Arachis hypogea, Cyanopsis tetragonoloba. Lablab purpureus, Cicer arietinum and the cereal Oryza sativa var. ponni by growing in soil amended with dried traditional and seaweed based Panchagavya. Experimental seedling recorded higher rates of linear growth of both shoots and roots as compared to controls and that too maximum growth was observed in seedling grown in soil amended with seaweed based Panchagavya at low concentration (1:100; Panchagavya; soil). A similar observation was made on the number of leaves produced, leaf area, number of root nodules formed in the pulses by rhizobia and increased the levels of all the enzymes.